TINJAUAN FILOSOFIS PERLINDUNGAN HAK MILIK ATAS MEREK - AGUNG SUJATMIKO (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
As part of Intellectual Property Rights, trademarks is an exclusive right. The rights contens two rights; to use and to license the trademarks. According to Jeremy Bentham all of property is based on utility or happiness for majority people. On the other hand, according to Rousseau the property has social functions. The philosophy aspects of trademarks as property can be used as guide that a trademark must be protected from infringement. The protection of trademarks is very important, because trademarks has economic value.